62‐4: Investigation of the Influence of Film Stress on Glass Strength. Issue 1 (28th June 2022) - Hu, Wencheng; Zhu, Zhengwei; Wang, Sheng; Lee, SeungKyu; Wang, Man; Ni, Jianwei
Abstract : In order to improve the strength of TFT glass, especially the surface strength of array side, we have studied the failure mechanism and influence factors of glass strength in this paper. The relationship between film stress and glass strength is proposed for the first time. By optimizing the parameters of array process and introducing negative (compressive) stress into passivation (PVX) layer, the surface strength of TFT glass could be increased substantially, and the degree of COG Mura can also be improved. Finally, a high‐performance and high‐strength TFT glass could be obtained.